2022
DOI: 10.32604/jrm.2022.017275
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Moso Bamboo Connections with External Clamp Steel Plates

Abstract: The Moso bamboo, a renewable green building material used in various new green buildings, have received extensive attention with the promotion of the concept of green buildings. To explore the mechanical properties of Moso bamboo connections with external clamp steel plates, the 16 specimens were designed by changing the bolt diameters and the end distances of the bolt holes. Their static tension tests were conducted to investigate bearing capacities and failure modes of different connection configurations. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
4
0
4
Order By: Relevance
“…Compared with the external clamp steel plate connection without filling grouting material [25], the bearing capacity of the connection with embedded steel plate and grouting material is improved. The average ultimate bearing capacity of the external clamp steel plate connection is 13 kN, while that of the embedded steel plate and grouting connection is 18.75 kN, which is 44.2% higher than that of the external steel plate connection.…”
Section: The Bearing Capacity Comparison With Other Connection Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the external clamp steel plate connection without filling grouting material [25], the bearing capacity of the connection with embedded steel plate and grouting material is improved. The average ultimate bearing capacity of the external clamp steel plate connection is 13 kN, while that of the embedded steel plate and grouting connection is 18.75 kN, which is 44.2% higher than that of the external steel plate connection.…”
Section: The Bearing Capacity Comparison With Other Connection Modesmentioning
confidence: 99%
“…Mechanical properties of Moso bamboos. Adapted with permission from reference[25], Copyright © 2022, Tech Science Press…”
mentioning
confidence: 99%
“…• Huecas, con aditamentos externos de refuerzo y sujeción La presencia de pernos que perforan al bambú produjo tres tipos de fallos (Nie et al, 2022): por cortante del perno (ruptura total), fallo dúctil (por aplastamiento o deformación del orificio bajo tensión continua) y fallo por punzonamiento (se fractura y se hunde la superficie exterior del bambú a ambos lados del perno). Estas fallas se produjeron a causa de los espacios que quedan en la superficie externa del bambú, entre los elementos que conforman la unión (culmo, perno y placas).…”
Section: Uniones Con Perforaciones En El Culmounclassified
“…Estas fallas se produjeron a causa de los espacios que quedan en la superficie externa del bambú, entre los elementos que conforman la unión (culmo, perno y placas). A mayor espacio, aumentó el riesgo de fallo (Nie et al, 2022). Estas condiciones propiciaron momentos de flexión adicionales por esfuerzos cortantes del perno, que falló al usar diámetros pequeños (M8 y M10).…”
Section: Uniones Con Perforaciones En El Culmounclassified
“…In view of the above problems, people have carried out a lot of work to explore [11]. Studies have shown that low molecular weight adhesives can enter a large number of broken cell cavities causing by the defibering process, which contributes to immobilize parenchyma cells in the subsequent process of hot pressing.…”
Section: Introductionmentioning
confidence: 99%